2010
DOI: 10.1016/j.ijsolstr.2009.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Void growth and coalescence in single crystals

Abstract: a b s t r a c tVoid growth and coalescence in single crystals are investigated using crystal plasticity based 3D finite element calculations. A unit cell involving a single spherical void and fully periodic boundary conditions is deformed under constant macroscopic stress triaxiality. Simulations are performed for different values of the stress triaxiality, for different crystal orientations, and for low and high work-hardening capacity. Under low stress triaxiality, the void shape evolution, void growth, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
71
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(83 citation statements)
references
References 63 publications
12
71
0
Order By: Relevance
“…The RVE simulations with a rate-dependent crystal plasticity model could reproduce the orientation dependent single crystal flow stress behavior of the bcc metal under two distinct constant stress triaxialities as reported in the previous work by Yerra et al [13] and as observed in general bcc metals. In other words, the crystal with the highest flow stress resulted in the earliest localization (or least uniform elongation corresponding to UTS point), while delayed localization for the lower flow stress when a void is included in the RVE.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…The RVE simulations with a rate-dependent crystal plasticity model could reproduce the orientation dependent single crystal flow stress behavior of the bcc metal under two distinct constant stress triaxialities as reported in the previous work by Yerra et al [13] and as observed in general bcc metals. In other words, the crystal with the highest flow stress resulted in the earliest localization (or least uniform elongation corresponding to UTS point), while delayed localization for the lower flow stress when a void is included in the RVE.…”
Section: Discussionsupporting
confidence: 66%
“…The number of the activated slip systems increases as the stress triaxiality increases. For example, additional six slip systems (2,3,8,9,13,19 slip systems in Table 1) are activated when the stress triaxiality is increased to 1. The activation of the slip system is further complicated when the void is embedded in the single crystal or at the boundary of bi-crystal.…”
Section: Slip System Activity (Resolved Sheaer Strain On the Slip Sysmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to anisotropic yielding (Hill, 1948;Barlat et al, 2005;Rousselier et al, 2012), some alloys also show anisotropic failure (Chen et al, 2009). A numerical representation of the microstructure coupled with damage models enabled Steglich et al (2008) to represent the anisotropic ductile fracture of an aluminium alloy, while Yerra et al (2010) numerically described the fracture inside a grain using a crystal plasticity material model around a spherical void. Recently, Luo et al (2012) proposed an anisotropic failure criterion based on a linear transformation of the plastic strain-rate tensor.…”
Section: Introductionmentioning
confidence: 99%